=-4-(6(2x-4)-6x)

Simple and best practice solution for =-4-(6(2x-4)-6x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for =-4-(6(2x-4)-6x) equation:


Simplifying
0 = -4 + -1(6(2x + -4) + -6x)

Reorder the terms:
0 = -4 + -1(6(-4 + 2x) + -6x)
0 = -4 + -1((-4 * 6 + 2x * 6) + -6x)
0 = -4 + -1((-24 + 12x) + -6x)

Combine like terms: 12x + -6x = 6x
0 = -4 + -1(-24 + 6x)
0 = -4 + (-24 * -1 + 6x * -1)
0 = -4 + (24 + -6x)

Combine like terms: -4 + 24 = 20
0 = 20 + -6x

Solving
0 = 20 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
0 + 6x = 20 + -6x + 6x
Remove the zero:
6x = 20 + -6x + 6x

Combine like terms: -6x + 6x = 0
6x = 20 + 0
6x = 20

Divide each side by '6'.
x = 3.333333333

Simplifying
x = 3.333333333

See similar equations:

| 0.25x=1228 | | 3x+2=12x-25 | | 1/3v-8/5=-3/2 | | 7x-12=11x-16 | | -4.6y+1.6=.6 | | -4.6+1.6=.6 | | 3x-7=-2x-5 | | 6x+19=11x-16 | | 4(3r-2)=4-12t | | 16t^2+9t-25=0 | | 1/8=7/56 | | -3+14-22=x | | 3b^2-60=0 | | -19x+Q=-19+P | | 72x5/8 | | 27/36=3/4 | | 0.3x+0.1(100-x)=180 | | |4-42|/2 | | -4(22/55)-3(10/55) | | 3*6=9*o | | 10x+15=11x+14 | | 9(13t+11)= | | 10=5/3v | | 175m-75m+48000=51000-150m | | 12/20=3/5 | | 8(13+15B)= | | 30x+10(100-x)=180 | | 5/2y=40 | | 12(11r-10)= | | 4y+2z-x= | | 16t^2+8t-80=0 | | 3(9a-6)= |

Equations solver categories